PENGARUH PENAMBAHAN TERUNG BELANDA DALAM PEMBUATAN VELVA LABU KUNING TERHADAP KARATERISTIK SENSORI - Wulandari, Friska Fris; Ayu, Dewi Fortuna; Johan, Vonny S (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was determine and obtain the optimal ratio between pumpkin and tamarillo for making velva. The study used a Completely Randomized Design with five treatments and three replications. The ratio of pumpkin and tamarillo 100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%. Data were analyzed statistically using Analysis of Variance and followed by Duncan’s New Multiple Range Test, test at 5% level. Results of ANOVA showed that the ratio of pumpkin and tamarillo significantly affected on descriptive and hedonic sensory test, such as of color, aroma, texture, and taste. The result of the descriptive test of the velva from the best treatment was a colour of reddish yellow, a bit scented of pumpkin and tamarillo, taste of pumpkin and tamarillo, and mildness texture, while hedonic test on colour, aroma, texture, and taste were liked by panelist. Keywords: Velva, pumpkin, tamarillo